2009
DOI: 10.1186/1752-1947-3-9304
|View full text |Cite
|
Sign up to set email alerts
|

Wear debris pseudotumor following total knee arthroplasty: a case report

Abstract: IntroductionIn patients who have undergone a total joint replacement, any mass occurring in or adjacent to the joint needs thorough investigation and a wear debris-induced cyst should be suspected.Case presentationAn 81-year-old man presented with a painful and enlarging mass at the popliteal fossa and calf of his right knee. He had had a total right knee replacement seven years previously. Plain radiographs showed narrowing of the medial compartment. Magnetic resonance imaging showed a cystic lesion at the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Nevertheless, there are two cases of soft tissue masses posterior to the implant following MoM TDR and one case of a wear debris induced pseudotumour seven years following TKA reported in the literature [3032]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are two cases of soft tissue masses posterior to the implant following MoM TDR and one case of a wear debris induced pseudotumour seven years following TKA reported in the literature [3032]. …”
Section: Discussionmentioning
confidence: 99%
“…Both of these materials are considered biocompatible but reaction still occurs within surrounding tissue and all metallic alloys will corrode over time, releasing metal ions . Indeed, several study reported high concentration of PE, Ti6Al4V, and CrCoMo wear debris on periprosthetic zones following implantation of MoPE or MoM prosthesis, demonstrating that none of these combinations are suitable . As a consequence, since the three past decades, new nonmetallic compounds such as polyetheretherketone (PEEK) and alumine ceramic (Al 2 O 3 ) are emerging.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Indeed, several study reported high concentration of PE, Ti6Al4V, and CrCoMo wear debris on periprosthetic zones following implantation of MoPE or MoM prosthesis, demonstrating that none of these combinations are suitable. 10,11,[17][18][19] As a consequence, since the three past decades, new nonmetallic compounds such as polyetheretherketone (PEEK) and alumine ceramic (Al 2 O 3 ) are emerging. PEEK belongs to the class of polymer and it is considered as a strong, elastic, inert, and biocompatible biomaterial since neither the bulk material nor its particulates generate an adverse biological response compared to other biocompatible biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] It is normally much less common after total knee replacement (TKR) because direct MoM contact is avoided, but can occur when the polyethylene surfaces of an implant have worn away. This can allow unintended MoM contact at the tibiofemoral 6,7 or patellofemoral interface with metal-backed patellar components, 8 or with constrained implants using MoM bushes. 9 Metallosis typically occurs as a late event in the life of a failing implant which has already experienced considerable polyethylene wear.…”
mentioning
confidence: 99%